Evaluation of a French adaptation of a community-based advance serious illness planning decision aid - Ariane Plaisance; Jennifer Mallmes; Anna Kamateros; Daren K. Heyland (Elsevier, 2023)
Objective: The Plan Well Guide™ (PWG) is a decision aid that empowers lay persons to better understand different types of care and prepares them, and their substitute decision-makers, to express both their authentic values and informed treatment preferences in anticipation of serious illness. We aimed to determine the acceptability of the newly translated French PWG and to evaluate decisional readiness and decisional conflict following its use by lay people. Methods: This is an acceptability and exploratory outcomes evaluation.Participants were requested to read and complete the French PWG and to engage in an online interview. We used the Acceptability Scale to determine the acceptability and the Preparation for Decision-making Scale and decisional conflict Scale to evaluate decisional readiness. Results: Forty-two (42) people participated. The average score on the Acceptability Scale was 18.1 (scale range: 4-20 [high-better]) and 26.6 on the Preparation for Decision-Making Scale (scale range: 6-30 [high-better]). A significant number of respondents reported needing more support to help them make better decisions. Conclusion: The French PWG has been deemed acceptable and relevant for lay people not currently facing clinical decisions. Innovation: The Plan Well Guide is innovative as it is the first decision aid empowering lay people for advance serious illness planning.